Criminalization of Individuals as a Deterrent Effect Upon Cartel Behaviour in Indonesia - Sibuea, Hengki M.; Silalahi, Udin; Budi, Henry Soelistyo (Journal of Judicial Review, 2024)
Cartel behavior is one of the activities that has received serious attention in Indonesian competition law. In some cases, cartels are also carried out by the same business actors, who in previous cases, have been found guilty of cartel. This article proposes that the optimal way to deal with cartels in Indonesia requires the imposition of criminal sanctions, such as imprisonment, against individuals who are responsible for the occurrence of cartels. Imprisonment will have a deterrent effect on the offenders of criminal acts. This paper is carried out with an analytical descriptive method with a normative legal approach by analyzing the Commission’s awards that punish the same business actors for repeatedly cartel offenses and also analyzing the laws and regulations of business competition and the Criminal Code as well as related laws and regulations applicable in Indonesia. The criminalization of individuals responsible for the occurrence of cartels is very urgent to be applied in Indonesia to provide a deterrent effect to cartel perpetrators.